PENINGKATAN KESUBURAN TANAH MEDITERAN DARI FORMASI BATUGAMPING GUNUNGKIDUL MELALUI APLIKASI PUPUK KANDANG SAPI - Nusantara, Alfonsus Eka Bara; Kautsar, Valensi; Noviyanto, Amir (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2025)
Gunungkidul Regency is one of the areas facing agricultural challenges, including the threat of drought and extremely low soil fertility. Low soil fertility is characterized by thin soil solum, sandy texture, and low organic matter content. Several efforts to improve soil fertility have been carried out using organic materials, particularly cow manure, which is abundantly available in the local community of Gunungkidul. This study aimed to evaluate the impact of organic fertilizer application on soil fertility. Soil samples were taken from Mediterranean soil that had developed on limestone formations in Gunungkidul. The research method used was an experimental approach, analyzing the changes in the soil's physical and chemical properties following the application of organic fertilizer. The experimental design included various ratios of Mediterranean soil material (K) to cow manure fertilizer (S) as follows: (i) Control (100% Mediterranean soil material and 0% cow manure); (ii) K1S3 (25%:75%); (iii) K2S2 (50%:50%); (iv) K3S1 (75%:25%). The results showed that the K1S3 treatment demonstrated the best performance during the incubation period and significantly improved soil fertility. The K1S3 treatment resulted in enhanced soil aggregate stability, an increase in pH to 7.73 (alkaline), an increase in soil organic carbon (C-organic) to 3.55% (high), an increase in total nitrogen (N-total) to 0.49% (medium), and an increase in total phosphorus (P-total) to 0.33% (medium). The study indicates that a higher application of organic material leads to greater improvements in soil chemical properties. Therefore, the use of cow manure as organic fertilizer can be an effective solution for improving the quality of calcareous soils in Gunungkidul.